2022
DOI: 10.3390/ijms23137253
|View full text |Cite
|
Sign up to set email alerts
|

Solo vs. Chorus: Monomers and Oligomers of Arrestin Proteins

Abstract: Three out of four subtypes of arrestin proteins expressed in mammals self-associate, each forming oligomers of a distinct kind. Monomers and oligomers have different subcellular localization and distinct biological functions. Here we summarize existing evidence regarding arrestin oligomerization and discuss specific functions of monomeric and oligomeric forms, although too few of the latter are known. The data on arrestins highlight biological importance of oligomerization of signaling proteins. Distinct modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
0
7
2
Order By: Relevance
“…An intriguing observation in these structural snapshots is novel dimer and trimer assemblies of βarrs. Although βarrs have strong propensity to adopt different oligomeric states (Chen et al, 2014;Chen et al, 2021;Gurevich and Gurevich, 2022), the dimer and trimer interfaces observed here differ significantly from previously reported interfaces (Chen et al, 2017;Chen et al, 2014;Chen et al, 2021) (Figure S7). The overall buried surface area in dimer and trimer assemblies are approximately 1500 Å 2 and 4500 Å 2 , respectively, suggesting a robust and stable oligomeric arrangement.…”
Section: Discussioncontrasting
confidence: 83%
“…An intriguing observation in these structural snapshots is novel dimer and trimer assemblies of βarrs. Although βarrs have strong propensity to adopt different oligomeric states (Chen et al, 2014;Chen et al, 2021;Gurevich and Gurevich, 2022), the dimer and trimer interfaces observed here differ significantly from previously reported interfaces (Chen et al, 2017;Chen et al, 2014;Chen et al, 2021) (Figure S7). The overall buried surface area in dimer and trimer assemblies are approximately 1500 Å 2 and 4500 Å 2 , respectively, suggesting a robust and stable oligomeric arrangement.…”
Section: Discussioncontrasting
confidence: 83%
“…An intriguing observation in these structural snapshots is novel dimer and trimer assemblies of βarrs. Although βarrs have a strong propensity to adopt different oligomeric states, 55 57 the dimer and trimer interfaces observed here differ significantly from previously reported interfaces 34 , 56 , 57 (Figure S7). The overall buried surface area in dimer and trimer assemblies are approximately 1,500 and 4,500 Å 2 , respectively, suggesting a robust and stable oligomeric arrangement.…”
Section: Discussioncontrasting
confidence: 72%
“…Stabilizing chaperones such as Fab30 may preferentially recognize some of these conformations better than the others. βarrs have a strong tendency to form various oligomeric states including dimers, trimers, tetramers, and even higher-order oligomers ( 54 , 55 ), although previous structures of βarr2 either bound to IP6 ( 56 ) or GPCR phosphopeptides have revealed trimers ( 17 ). Future work should explore whether the dimeric arrangement observed here is specific to D6R.…”
Section: Discussionmentioning
confidence: 99%